The Role of Critical Thinking and Executive Function in Misconceptions in Psychology - Murti, Heru Astikasari Setya; Hastjarjo, Thomas Dicky; Patria, Bhina (Jurnal Psikologi, 2021)
Misconception in psychology is a belief that is broadly contradicting to scientific evidence and is particularlycommon in the field of psychology. It is important to study misconceptions in psychology considering thecontribution of the effort to provide education or to demonstrate rejection of fallacies of popular ideas/themes.Misconceptions in psychology relates to critical thinking as well as the executive function (EF) that controls andregulates cognitive processes. This research aims to determine the role of critical thinking and EF (cognitiveflexibility, working memory, and inhibitory control) with misconceptions in psychology. This study used non-experimental methods, using test (paper and pencil) and PEBL/ Psychology Experiment Building Language(computerized). The sampling technique used was convenience sampling. The subjects in this study were 153psychology students, consisting of 105 students from Universitas Gadjah Mada (UGM) and 48 students fromUniversitas Negeri Yogyakarta (UNY). Instruments that were used for data collection were the misconception inpsychology test, critical thinking test, Wisconsin/Berg Card Sorting Test (WCST/BCST), Backward Digit Span,and Stroop Test. There is no correlation between cognitive flexibility and misconceptions in psychology, socognitive flexibility is not included in the calculation of hierarchical regression analysis. Based on the results ofhierarchical regression analysis, it can be concluded that the role of inhibitory control on psychologicalmisconceptions is 11.4%, Î”R2 = .114; b* = .33; t(149) = 4.52, p < .001; the role of working memory is 3%, Î”R2 =.030; b* = -.16; t(149) = -2.19, p = .03; and the role of critical thinking is 2.6%, Î”R2 = .026; b* = -.19; t(149) = -2.53, p = .01.